THEORETICAL EVALUATION OF THE POTENTIAL OF INFOGRAPHICS AS POWERFUL TOOLS IN ENGLISH LANGUAGE TEACHING - Korniush, Hanna (Problems of Engineer-Pedagogical Education, 2020)
The present article sheds light on the opportunities that using infographics in the ELT classroom offers. The author of the paper dwells upon the definition of the term “infographics” and explains why an infographic is an effective and powerful medium of instruction in the contexts of blended learning and edutainment, which are currently gaining more and more popularity. Particular attention is paid to the advantages of incorporating infographics in the educational process, with special emphasis being placed on the benefits of infographics for better English language teaching and learning. Furthermore, the author suggests a number of ways of using infographics to develop students’ four core English language skills which are reading, writing, listening and speaking, expand their vocabulary and improve their grammar knowledge while optimizing retention and maintaining learners’ constant interest in what is being studied. The article also explains how getting students to create their own infographics can boost their skills and competences. It is highlighted that using computer and mobile applications or any available online programs and platforms to design an appealing informative picture will definitely benefit students’ critical thinking skills (which are believed to be essential in the 21st century), info-digital literacy (which is claimed to be indispensable in a knowledge society characterized by information overload, total informatization and computerization of all spheres of life) and note-taking skills (which help learners better see connections between concepts, processes or things, structure and record ideas). A few recommendations are made regarding what to take into consideration and what stages teachers and students are expected to go through while creating an infographic. The article finishes with a few suggestions concerning prospects for further scientific research in the field of practical verification of the effectiveness of incorporating infographics in the ELT blended learning environment.